Assessment of Groundwater Recharge Sources And Their Dynamics Using Environmental Isotope And Hydrochemical Approaches In Coastal Aquifers of Peninsular Malaysia - ROSLANZAIRI MOSTAPA; KAMARUDIN SAMUDING; JEREMY ANDY DOMINIC DAUNG; MOHD MUZAMIL MOHD HASHIM; NEERAJ PANT (ASM Science Journal, 2022)
The aims of this study are to investigate the interconnection and the dynamics between groundwater and surface water in the coastal area in the eastern part of Peninsular Malaysia using isotope technique integrated with the hydrochemical and hydrogeological approach. Using stable isotopic composition (d2H and d18O), it was shown that there is no relationship between the mid–deep and deep groundwater indicating that they came from different aquifers. Based on the two–component mass balance for oxygen, the source of groundwater salinity was determined. The results showed that 12% of the groundwater is recharged by the seawater while 88% is from both rainwater and river water. This reveals that one of the deep groundwater (UMPB) was affected by seawater intrusion. However, the deep groundwater in the southern part of the study area was not influenced by saline water because of the geological conditions. As a result of the seawater intrusion, UMPB is showing the characteristics of shallow groundwater due to mixing with modern saline water which was also supported by the natural radioactive isotope (3H and 14C) and hydrochemical results.